PTSD Risk Factors and Acute Pain Intensity Predict Length of Hospital Stay in Youth after Unintentional Injury - Anna Monica Agoston; Amina Bhatia; John C. Bleacher; Alexis Smith; Karen Hill; Susanne Edwards; Alicia Cochran; Maia Routly (MDPI AG, 2022)
Background: Many hospitals have adopted screening tools to assess risk for posttraumatic stress disorder (PTSD) after pediatric unintentional injury in accordance with American College of Surgeons recommendations. The Screening Tool for Early Predictors of PTSD (STEPP) is a measure initially developed to identify youth and parents at high risk for meeting diagnostic criteria for PTSD after injury. Acute pain during hospitalization has also been examined as a potential predictor of maladaptive outcomes after injury, including PTSD. We investigated in a retrospective cohort study whether the STEPP, as well as acute pain intensity during hospitalization, would predict maladaptive outcomes during the peri-trauma in addition to the post-trauma period, specifically length of hospitalization. Methods: A total of 1123 youths aged 8-17 (61% male) and their parents were included. Patients and parents were administered the STEPP for clinical reasons while hospitalized. Acute pain intensity and length of stay were collected through retrospective chart review. Results: Adjusting for demographics and injury severity, child but not parent STEPP total predicted length of stay. Acute pain intensity, child threat to life appraisal, and child pulse rate predicted length of stay. Conclusions: Acute pain intensity and child PTSD risk factors, most notably child threat to life appraisal, predicted hospitalization length above and beyond multiple factors, including injury severity. Pain intensity and child appraisals may not only serve as early warning signs for maladaptive outcomes after injury but also indicate a more difficult trajectory during hospitalization. Additional assessment and treatment of these factors may be critical while youth are hospitalized. Utilizing psychology services to support youth and integrating trauma-informed care practices during hospitalization may support improved outcomes for youth experiencing unintentional injury.